2013
DOI: 10.1589/jpts.25.237
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Intervertebral Body Angle of the Lower Cervical Spine during Protracted Head Extension Using Measured by Fluoroscopy

Abstract: Abstract.[Purpose] To analyze dynamic lower cervical spine kinematics under neutral head extension (Ex) and protracted head extension (Pro-Ex) using fluoroscopy.[Method] The intervertebral body angle of the lower cervical spine of 8 healthy individual was analyzed using fluoroscopy during cervical extension with the head in the neutral (Ex) and protracted (Pro-Ex) positions.[Results] At maximum cervical extension position, we noted a significanly smaller value in the Pro-Ex position than in Ex position. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Generally, degenerative changes frequently occur in lower segments 14 ) . Our previous study 7 ) showed that a protracted position during head extension also creates a higher ROM of the intervertebral body angle at the C5–6 and C6–7 levels. Considering these results, we assumed the Pro position is one of the strong reasons for degenerative changes in the C6–7 segments.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Generally, degenerative changes frequently occur in lower segments 14 ) . Our previous study 7 ) showed that a protracted position during head extension also creates a higher ROM of the intervertebral body angle at the C5–6 and C6–7 levels. Considering these results, we assumed the Pro position is one of the strong reasons for degenerative changes in the C6–7 segments.…”
Section: Discussionmentioning
confidence: 92%
“…These images were analyzed using the LabVIEW software (National Instruments, Austin, TX, USA). For kinematic analysis, the intervertebral body angles were analyzed based on our previous study 7 ) . The intervertebral body angle is the angle between the midplane of the adjacent vertebral spine as described by Frobin et al 6 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cervical spine has the largest mobility of all sectors of the human spine. Since the head moves with six degrees of freedom relative to the thorax, the cervical spine has six degrees of freedom [ 17 , 37 , 46 ]. The range of motion differs between directions.…”
Section: Neck Modelmentioning
confidence: 99%
“…The prototype 56 system was shown to be valid, although the reliability of the repositioning and upper cervical 57 flexion tests needs to be reconsidered. The anatomical and physiological characteristics of the cervical spine allow humans to rotate 65 and translate their head relative to the thorax in all directions (six degrees of freedom) 66 (Ordway et al, 1997;Park, 2015;Seo et al, 2013). Impairment of the neck is related to the 67 cervical range of motion (Ernst et al, 2015;Hall et al, 2010).…”
Section: Abstract 38mentioning
confidence: 99%